The Pythagorean Triple Two Ways!

A Pythagorean triple ( a , b , c ) (a,b,c) is referred to three natural numbers a a , b b , and c c , such that a 2 + b 2 = c 2 a^2 + b^2 = c^2 . How many Pythagorean triples with the largest of three numbers less than 100 100 exist such that there is also a Pythagorean triple ( o , n , m ) (o,n,m) such that m : n : o = 1 a : 1 b : 1 c m:n:o = \frac 1a : \frac 1b : \frac 1c ?

Example: For the triple ( 3 , 4 , 5 ) (3,4,5) , 1 5 : 1 4 : 1 3 \frac 15 : \frac 14 : \frac 13 cannot be the ratio of a Pythagorean triple, because 1 25 + 1 16 1 9 \frac 1{25} + \frac 1{16} \ne \frac 19 .

0 5 1 4 3 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Apr 23, 2020

Let the Pythagorean triple ( m , n , o ) (m,n,o) be m < n < o m<n<o . Then we have to prove if there is solution for

1 o 2 + 1 n 2 = 1 m 2 o 2 + n 2 o 2 n 2 = 1 m 2 Note that m 2 + n 2 = o 2 m 2 + 2 n 2 m 2 n 2 + n 4 = 1 m 2 m 4 + 2 m 2 n 2 = m 2 n 2 + n 4 Divide both sides by m 2 n 2 m 2 n 2 + 2 = 1 + n 2 m 2 m 2 n 2 + 1 n 2 m 2 = 0 Multiply both sides by m 2 n 2 ( m 2 n 2 ) 2 + m 2 n 2 1 = 0 m 2 n 2 = 5 1 2 Since m 2 n 2 > 0 \begin{aligned} \frac 1{o^2} + \frac 1{n^2} &= \frac 1{m^2} \\ \frac {o^2+n^2}{o^2n^2} & = \frac 1{m^2} & \small \blue{\text{Note that }m^2+n^2=o^2} \\ \frac {m^2+2n^2}{m^2n^2+n^4} & = \frac 1{m^2} \\ m^4 + 2m^2n^2 & = m^2n^2+n^4 & \small \blue{\text{Divide both sides by }m^2n^2} \\ \frac {m^2}{n^2} + 2 & = 1 + \frac {n^2}{m^2} \\ \frac {m^2}{n^2} + 1 - \frac {n^2}{m^2} & = 0 & \small \blue{\text{Multiply both sides by }\frac {m^2}{n^2}} \\ \left(\frac {m^2}{n^2}\right)^2 + \frac {m^2}{n^2} - 1 & = 0 \\ \frac {m^2}{n^2} & = \frac {\sqrt 5-1}2 & \small \blue{\text{Since }\frac {m^2}{n^2}>0} \end{aligned}

There is no rational solution for m n \dfrac mn , hence the required natural number triple ( m , n , o ) (m,n,o) does not exist.

So this solution looks really cool, however, the problem can be solved WAY earlier in your explanation. You say that ab = m^2 - n^2, and ac = m^2 + n^2. Note that m^2 + n^2 and m^2 - n^2 must be relatively prime ( you can assume that a,b,c are primitive as if not, just use different variables). But if those 2 are relatively prime, then why do they have a common? a obviously must be greater than 1, and that's the proof done!

Arindam Kulkarni - 1 year, 1 month ago

Since m : n : o = 1 a : 1 b : 1 c m:n:o=\dfrac{1}{a}:\dfrac{1}{b}:\dfrac{1}{c} , therefore we have to have ( a b ) 2 + ( a c ) 2 = ( b c ) 2 (ab) ^2+(ac) ^2=(bc)^2 . So a b = m 2 n 2 , b c = 2 m n , c a = m 2 + n 2 ab=m^2-n^2, bc =2mn, ca =m^2+n^2 for some relative prime integers m m and n n . Then b ( c + a ) = 2 m 2 , b ( c a ) = 2 n 2 b 2 ( c 2 a 2 ) = 4 m 2 n 2 b 4 = 4 m 2 n 2 b 2 = 2 m n b(c+a)=2m^2, b(c-a)=2n^2\implies b^2(c^2-a^2)=4m^2n^2\implies b^4=4m^2n^2\implies b^2=2mn . Since ( a , b , c ) (a, b, c) is a Pythagorean triplet, therefore a = p 2 q 2 , b = 2 p q , c = p 2 + q 2 a=p^2-q^2, b=2pq, c=p^2+q^2 for some integers p , q p, q . This implies m n = 2 p 2 q 2 mn=2p^2q^2 . So one of m , n m, n must be an odd square multiple of 2 2 , and the other must be an odd square. Let m = 2 ( 2 r + 1 ) 2 , n = ( 2 s + 1 ) 2 m=2(2r+1)^2, n=(2s+1)^2 . Then b = 2 ( 2 r + 1 ) ( 2 s + 1 ) , a = 4 ( 2 r + 1 ) 4 ( 2 s + 1 ) 4 2 ( 2 r + 1 ) ( 2 s + 1 ) , c = 4 ( 2 r + 1 ) 4 + ( 2 s + 1 ) 4 2 ( 2 r + 1 ) ( 2 s + 1 ) b=2(2r+1)(2s+1), a=\dfrac{4(2r+1)^4-(2s+1)^4}{2(2r+1)(2s+1)}, c=\dfrac{4(2r+1)^4+(2s+1)^4}{2(2r+1)(2s+1)} . But then neither a a , nor c c is an integer, since the numerator of each of them is odd and the denominator is even. Hence there is no such triplet ( a , b , c ) (a, b, c) satisfying the conditions of the problem. That is, the number of such triplets is 0 \boxed 0 .

So this solution looks really cool, however, the problem can be solved WAY earlier in your explanation. You say that ab = m^2 - n^2, and ac = m^2 + n^2. Note that m^2 + n^2 and m^2 - n^2 must be relatively prime ( you can assume that a,b,c are primitive as if not, just use different variables). But if those 2 are relatively prime, then why do they have a common? a obviously must be greater than 1, and that's the proof done!

Arindam Kulkarni - 1 year, 1 month ago
Arindam Kulkarni
Apr 22, 2020

For any triple (a,b,c), say the ratio is x : y : z x:y:z , where they are all relatively prime. They MUST all be relatively prime because if 2 of them have a common factor greater than 1, then the other will also have that factor by pythagorean theorem. Every pythagorean triple must have this 'primitive' triple, where all sides are relatively prime.

Now, if a triple had terms in a ratio of 1 x \frac {1}{x} : 1 y \frac {1}{y} : 1 z \frac {1}{z} , it will be in a ratio of y z : x z : x y yz:xz:xy . Obviously, this is not primitive, since as discussed above, if 2 have a common prime factor, the third does as well. However, while each pair does have a common factor, all 3 should not, as x , y , z x, y, z are relatively prime, and thus if y z yz and x z xz have z in common, x y xy should NOT have z in common. Therefore, this cannot be a pythagorean triple, and thus the answer is 0 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...